The integration of maritime culture in the preparation of contextualized reading instruction using community as learning laboratory (CoLLab) model - Abadiano, Justine V (University of the Philippines Visayas, 2022)
This study documented the experience in developing contextualized reading materials for Junior High School students using the maritime cultural contents of Barangay Culasi, Roxas City, Philippines as context. following the phases of Community as Learning Laboratory (CoLLab) Model of Gadong, et. al. (2017), the researcher gathered the maritime cultural contents in fishing methods and practices through community exposure activities, observations, interviews and interactions with the locals and community leaders. Collaboration with the " more knowledgeable others" from the academe and the community education leader in a workshop provided an outline of contexts for the integration of maritime culture in the preparation of remedial reading instruction to address the need for improved reading competencies among Grade 7 students. Teachers developed six reading materials integrated with local maritime cultural contents and designed six lesson plans in 5Es format of constructivism. The reading materials were then subjected to readability testing, language review, and subsequently, resulted in a score of 3.73 using the material evaluation checklist of Dickinson (2010) indicating that the materials are highly acceptable for use and delivery. When asked as to how the materials can be utilized as supplementary reading materials, teacher-evaluators proposed that these could be used for reading remediation programs, diagnostic asessments and reading activities that demand local culture as context. Suggestions about the layout, design and content were included.